In situ synthesis of Au-shelled Ag nanoparticles on PDMS for flexible, long-life, and broad spectrum-sensitive SERS substrates. Issue 82 (18th September 2017) - Fortuni, B.; Inose, T.; Uezono, S.; Toyouchi, S.; Umemoto, K.; Sekine, S.; Fujita, Y.; Ricci, M.; Lu, G.; Masuhara, A.; Hutchison, J. A.; Latterini, L.; et al.
Abstract : A simple, fast, one-step fabrication of silver nanoparticles with atomically thin gold coatings on polydimethylsiloxane affords oxidation-resistant and highly sensitive surface enhanced Raman scattering (SERS) substrates. Abstract : A simple and fast one-step fabrication method of silver nanoparticles (AgNPs) on a polydimethylsiloxane (PDMS) film and their improvement as highly sensitive surface enhanced Raman scattering (SERS) substrates via atomically thin Au coatings is demonstrated. The thin Au layer provides oxidation resistivity while maintaining the broad spectral range SERS sensitivity of Ag nanoparticles.